Metastatic gastric adenocarcinoma associated with hypertrophic gastropathy resembling Ménétrier’s disease in an adult Labrador Retriever dog - Sarandy, Thais Barroso; Lopes, Carlos Eduardo Bastos; Piero, Fábio Del; Ecco, Roselene (Brazilian Journal of Veterinary Pathology, 2021)
We describe a case of hypertrophic gastropathy (Ménétrier’s like disease) with metastatic gastric adenocarcinoma in a seven-year-old intact female Labrador Retriever dog. The animal suddenly presented with emesis and died. Gross lesions included a marked diffuse thickening of the gastric mucosa and an ulcerated transmural neoplastic mass in the gastric body. Gastric body and fundus were affected by foveolar hyperplasia with loss of chief and parietal cells replaced by mucous cells and marked dilatation of gastric glands. An area of gastric adenocarcinoma with submucosal lymphatic vessels invasion was also present and metastases were observed in the gastric lymph nodes, small intestine, pancreas, lung and liver. Due to its similarity with other gastric proliferative disorders, including this condition in the list of differentials is a necessary step in the diagnostic investigation of canine gastropathies.